Conceptos basicos de fisiologia del frijol - White, J.W. (United Nations Development Programme, 1985)
The physiological processes that determine bean growth are reviewed, namely photosynthesis, respiration, DM distribution, HI, yield components, and environmental effects. Some concepts used in physiological work such as growth analysis, leaf area determination, data analysis, yield, yield components, and environmental data are discussed. (CIAT)